Humanising Pedagogy within Higher Education: A Ten-Year Scoping Literature Review - Curwyn Mapaling; Christopher Norman Hoelson (University of Johannesburg, 2022)
Humanising pedagogical practices calls for the integration of decolonial theoretical perspectives that are informed by subjective social realities and a social justice approach to educational research. This scoping literature review sought to establish the state of research on humanising pedagogy within higher education over a period of ten years, namely 2010 to 2020. We searched numerous electronic databases using a variety of relevant search terms. Studies included were published in English over the ten-year period and were all related to humanising pedagogy within higher education. A total of 11 articles and three scholarly books met the inclusion criteria. The study identified that humanising pedagogy is an emerging field of study as only a limited number of primarily conceptual articles were published during the study period. For the data synthesis, we utilised a thematic analysis approach. The results from the thematic analysis suggest that decoloniality and social justice, engaged principles and practices, and curiosity and creativity could have implications for the global South and pedagogical development in previously colonised educational and cultural heritage settings. Further research should be informed by methodological approaches congruent with social justice imperatives to advance empowered knowledge and research in this field.